Eye Movements and the Intraorbital Subarachnoid Space: Potential Contribution of Altered Cerebrospinal Fluid Pumping in Optic Neuropathies - Demer, Joseph L.; Clark, Robert A.; Suh, Soh Youn; Giaconi, JoAnn A.; Nouri-Mahdavi, Kouros; Law, Simon K.; Bonelli, Laura; Arnold, Anthony C.; Quiros, Peter; Coleman, Anne L.; Caprioli, Joseph (Investigative ophthalmology & visual science, 2025)
The optic nerve (ON) is mechanically perturbed by eye movements that shift cerebrospinal fluid (CSF) within its surrounding dural sheath. This study compared changes in ON length and CSF volume within the intraorbital ON sheath caused by eye movements in healthy subjects and patients with optic neuropathies. Twenty-one healthy controls were compared with 11 patients having primary open angle glaucoma (POAG) at normal intraocular pressure (IOP), and 11 with chronic non-arteritic anterior ischemic optic neuropathy (NA-AION). High resolution magnetic resonance imaging (MRI) was performed in central and eccentric gazes, and analyzed to determine ON partial volume and gaze-related changes in ON path redundancy, ON elongation, and intrasheath CSF volume. ON volume was subnormal in both POAG and NA-AION. In all subjects, ON path redundancy decreased similarly from abduction to central gaze to adduction; in healthy subjects, the ON path was also significantly less redundant in infraduction and supraduction. The ON elongated significantly in adduction in controls and NA-AION but not in POAG. In all groups, CSF volume was 40 to 50 mm3 in central gaze, and significantly decreased in adduction, abduction, and supraduction in controls but subnormally in adduction only in POAG and NA-AION. The globe translated laterally more than normal in NA-AION but did not retract. Horizontal gaze and supraduction change subarachnoid CSF volume around the retrobulbar ON. Eye movements might thus pump CSF to promote ON health, but this effect is subnormal in adduction in POAG and NA-AION, suggesting that retrobulbar CSF pumping is associated with chronic forms of these optic neuropathies.